Stakeholder and quality management in regional sports tourism (RST) networks - Vejchoda, Philipp (2018)
Sport tourism as a field has undergone various changes during the last decades. More and more organizations (for-profit, not-for-profit, public) have entered this market and research suggests that this development will continue over the next years.